’CASE STUDY, DYNAMIC CAPABILITIES AND UPSTREAM STRATEGY: SUPERMAJOR EXP - P. W. WOLU, MJURU; F. K. NOM (International Journal of Multidisciplinary Research and Studies, 2021)
This case study explicates the dynamic capabilities framework and shows its relevance for the worldwide Exploration Division of a significant IOC, Supermajor EXP. Three characteristics of dynamic capabilities are described: (1) how they differ from ordinary capabilities; (2) how they’re identified, built, and strengthened through managerial processes; and (3) how they function throughout the strategy development and execution process (sensing, seizing and transforming). Over a one-year period, EXP implemented key organizational and business model innovations to spot and start to manage 10 dynamic capabilities. The case demonstrates how EXP identified and prioritized their dynamic capabilities through a strategic assessment, built, strengthened, and evolved them through dialogical, collaborative, and iterative processes that were informed by learning, sustained them by establishing new organizational structures, and reinforced them through cultural initiatives. Three of EXP’s dynamic capabilities are described in detail: (1) accuracy in volume and risk predictions in investment proposals (the degree to which the subsurface reality is exposed when the well is drilled); (2) strategic deployment of talent into the ventures and projects with the best measure (right people, within the right seats, doing the proper thing, with the correct people, at the proper time), and (3) effective management of the centralized–decentralized polarity.